2022
DOI: 10.3390/s22176633
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Stress Monitoring Using Biomarkers and Smartwatches: A Systematic Review

Abstract: This article presents a systematic review of the literature concerning scientific publications on wrist wearables that can help to identify stress levels. The study is part of a research project aimed at modeling a stress surveillance system and providing coping recommendations. The investigation followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. In total, 38 articles were selected for full reading, and 10 articles were selected owing to their alignment with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 39 publications
0
6
0
2
Order By: Relevance
“…In addition, they showed that the performance of a fall detection algorithm could be strongly dependent on the smartwatch model Auepanwiriyakul et al (2020) [ 34 ] / UK Combined methods design 15 healthy volunteers This study evaluated raw IMU sensor data quality, followed by a trial of the feasibility of wearable health devices in a clinical environment In this study, wearable IMU technology, such as smartwatches and research-grade IMU Xsens, was cleaner linear acceleration signals and fewer errors than Axivity due to additional magnetometer and strap-down integration technology. This technology is viewed positively by healthcare professionals, according to this study on its acceptability among hospital patients Varghese et al (2021) [ 35 ] / Germany Prospective study 400 participants This study was a prospective study from 2018 to the end of 2021, in which they recruited and measured the hand movements of 400 participants using Apple smartwatches and smartphones. The aim was to distinguish PD from other movement disorders and healthy individuals Results showed that smartwatches had high agreement with seismological sensor validation in measuring movement subtleties or hand-tremor amplitudes and frequencies more accurately than clinical documentation or human vision
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…In addition, they showed that the performance of a fall detection algorithm could be strongly dependent on the smartwatch model Auepanwiriyakul et al (2020) [ 34 ] / UK Combined methods design 15 healthy volunteers This study evaluated raw IMU sensor data quality, followed by a trial of the feasibility of wearable health devices in a clinical environment In this study, wearable IMU technology, such as smartwatches and research-grade IMU Xsens, was cleaner linear acceleration signals and fewer errors than Axivity due to additional magnetometer and strap-down integration technology. This technology is viewed positively by healthcare professionals, according to this study on its acceptability among hospital patients Varghese et al (2021) [ 35 ] / Germany Prospective study 400 participants This study was a prospective study from 2018 to the end of 2021, in which they recruited and measured the hand movements of 400 participants using Apple smartwatches and smartphones. The aim was to distinguish PD from other movement disorders and healthy individuals Results showed that smartwatches had high agreement with seismological sensor validation in measuring movement subtleties or hand-tremor amplitudes and frequencies more accurately than clinical documentation or human vision
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…The performance of stress level monitoring systems is crucial to ensure accurate and reliable measurements. Here are some key aspects to keep in mind while evaluating the performance of stress level monitoring 38,39 :…”
Section: F I G U R E 7 Progression Of Biosensors Toward Wearable (Lim...mentioning
confidence: 99%
“…que podem ser medidas através de sensores para auxiliar na identificação do estresse ocupacional [12]. Os sinais físicos de estresse podem ser medidos através da sudorese excessiva, temperatura da pele, alterações de frequência cardíaca e respiração ofegante, por exemplo [13]. Uma pesquisa recente está buscando uma maneira de identificar a presença de estresse através de outros biomarcadores contidos na saliva: cortisol, testosterona, dehidroepiandrosterona (DHEA) e sulfato de dehidroepiandrosterona (SDHEA) [14].…”
Section: Estresse Ocupacionalunclassified
“…Aspectos emocionais para o reconhecimento de estresse: existem alterações fisiológicas, emocionais e cognitivas que influenciam as alterações manifestadas pelo estresse, estas alterações podem ser um estado de distress quando é negativo, ou eustress quando é positivo. Apesar dos resultados importantes dos biomarcadores apresentados recentemente [12,13], pesquisas nessa área ainda precisam avançar para que sistemas computacionais sejam capazes de identificar as alterações emocionais e cognitivas, para então diferenciar os dois momentos de estresse. Para a identificação do estresse, normalmente são aplicadas metodologias baseadas em questionários e escores, como por exemplo, os trabalhos relacionados a avaliação dos profissionais de saúde [15,16].…”
Section: Estresse Ocupacionalunclassified